Multidisciplinary characterisation, weathering patterns, and durability assessment of stone blocks for the conservation of Tamentfoust fort (ex. Rusguniae) in Algiers. (Fracture and Structural Integrity, 2025)
This study investigates the physico-mechanical properties, mineralogical composition, deterioration processes, weathering patterns, and durability of building materials in the Ottoman Fort of Tamentfoust, Algiers, to inform heritage conservation strategies. Stone block samples were taken from a highly damaged wall and, the mechanical and physical characterisation was carried out with through laboratory and on-site methods. These methods included destructive tests (compressive and flexural strength) and non-destructive techniques (Schmidt hammer rebound, ultrasonic pulse velocity, thermal imaging, density, porosity, and capillarity coefficients. Mineralogical and petrographical analyses were conducted using X-ray diffraction (XRD) and X-ray fluorescence (XRF), while durability was evaluated through sodium chloride crystallization and hydrogen chloride ageing tests, with scanning electron microscopy (SEM-EDX) analysing microstructural properties. Weathering forms were assessed and documented using 3D laser scanning, thus generating a weathering mapping for the most damaged facade. The results revealed two stone types: one with high porosity, low strength, and poor durability, and another with high compactness and excellent durability. These findings provide critical insights into material behaviour, enabling tailored preservation strategies for the fort and contributing to the broader field of heritage conservation.
Keywords: Stone building heritage; conservation; chemical, physical and mechanical characterisation,; durability and weathering mapping